Development of The Mangrove Environmental Sustainability Strategy (Mess) Model as an Integration of Business And Environmental Conservation - Arifin, Mohammad; Utami, Evi Farsiah; Kusumaningtyas, Desita Rizky Amelia (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2024)
The development of this model is necessary to achieve a balance between business interests and environmental conservation by integrating local business needs with mangrove conservation efforts. This model supports sustainable management, improves the welfare of local communities, and supports the Sustainable Development Goals. This research prioritizes efforts to design a comprehensive and integrated framework for managing mangrove ecosystems. This research design combines quantitative and qualitative approaches. A quantitative approach is used to collect numerical data related to relevant business and environmental aspects. A descriptive approach is used to provide a detailed picture of the existing conditions and dynamics of local business interests as well as environmental conservation efforts in the mangrove areas studied. The results of the research application show that there is a balance between mangrove tourism exploration and environmental sustainability and conservation.